Symposium 1: Networked Learning and Identity development in open online spaces - Cronin, Catherine (Proceedings of the International Conference on Networked Learning, 2014)
Higher education is responding to multiple challenges in the current context of mobile networking, openness, and participatory culture. This paper explores emerging open education practices in higher education. The affordances of open online spaces are compared with those of physical classrooms and bounded online spaces. It is argued that open online spaces can be considered a Third Space in which students can construct their identities and develop their networks, integrating formal and informal learning, and developing literacies for lifelong learning.